KARAKTERISTIK EDIBLE FILM YANG DIHASILKAN DENGAN BAHAN DASAR PEKTIN KULIT BUAH KOPI ROBUSTA DAN GLUKOMANAN - Firda Ilma Dea; Ike Sitoresmi Mulyo Purbowati; Condro Wibowo (AGROINTEK, 2022)
Coffee peel is a by-product of coffee processing, which is about 50-60%. The coffee peel has pectin content ranging from 27.20 to 57.24%. One of the utilization of this pectin was used as a raw material for an edible film. Pectin-based edible films had advantages, including good tensile strength and water vapor transmission rate properties. On the other hand, edible film pectin had weaknesses: hard, brittle, and low in elongation, so it was necessary to add other ingredients, such as glucomannan and sorbitol, to correct these weaknesses. This study aimed to determine the best characteristics of the edible film of Robusta coffee skin pectin with glucomannan and the addition of sorbitol. This research was an experimental method using a completely randomized design method with two factors: the ratio of pectin: glucomannan 1:4, 2:3, and 3:2; addition of sorbitol 1.5 ml, 3 ml, and 4.5 ml. The observed variables included the thickness, solubility, and water vapor transmission rates. Data of thickness, solubility, and water vapor transmission rate were analyzed using analysis of variance and further tested by the Duncan Multiple Range Test at a 5% level. The selected treatment for producing the edible film from pectin of coffee peel and glucomannan was R3K1. The characteristics of the edible film produced were a thickness value of 0.11 mm, solubility of 72.3%, water vapor transmission rate of 5,77 gram/m2, the tensile strength of 2.05 Mpa, and elongation of 13.71%.